Assessment of ergonomics risk in typical upper limb operations of electricians based on RULA - Zekai LIANG; Guanlin LI; Shiheng ZHU; Jiajie LI; Qingsong CHEN (环境与职业医学)
BackgroundA large number of power supply workers are involved in live working and are exposed to multiple risk factors for long periods of time during outdoor work, which in turn causes occupational health problems. ObjectiveTo identify potential ergonomic factors related to work-related musculoskeletal disorders (WMSDs) and estimate the ergonomic risk of electricians. MethodsA total of 31 workers were randomly selected from a training base under a power supply enterprise in Guangxi, and their operation processes were recorded by video. Using the Rapid Upper Limb Assessment (RULA) method, the workers were scored by the posture of their arms, neck, and torso during operation, and the final scores were summarized to assess their risk level. Two independent samples t-tests were used to compare the differences in RULA scores. ResultsA total of 31 videos for mounting/dismounting insulation mask and 29 videos for breaking/connecting contact terminal were collected. The RULA score for mounting/dismounting insulation mask was 6.6 ± 0.7 (left side) and 7.0 ± 0.2 (right side), most of the workers had a score of 7 (71.0% on the left side and 96.8% on the right side), and the upper limb and overall scores on the right side were higher than those on the left side (P < 0.05). The RULA score for breaking/connecting contact terminal was 6.9 ± 0.4 (both right and left sides), most of workers had a score of 7 (89.7% on the left side and 93.1% on the right side), and the difference of the overall scores between the right and left side for this operation were not statistically significant (P > 0.05). The ergonomic risk levels for both operations were level 3 or higher. ConclusionMounting/dismounting insulation mask and breaking/connecting contact terminal are typical upper limb operations, and have a high level of ergonomics risk, requiring effective preventive and protective measures.